2002
DOI: 10.5014/ajot.56.4.380
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Instructions on Functional Reach in Persons With and Without Cerebrovascular Accident

Abstract: One clinical implication is that internally focused instructions can contribute to slower and less forceful reach in adults with and without CVA. This research reinforces the need for therapists to consider their use of instruction during the evaluation and treatment of movement disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
1
11

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(99 citation statements)
references
References 18 publications
5
79
1
11
Order By: Relevance
“…The movement characteristic most frequently studied has been the smoothness in terms of the peak number in the hand velocity profile during the movement (Butler et al, 2010;Cacho et al, 2011;Chang et al, 2005;Fasoli et al, 2002;Kamper et al, 2002;Merlo et al, 2013;Murphy et al, 2011Murphy et al, , 2013. However, one study has shown that this metric couldn't be robust against noise or other factors, proposing an analysis of the movement smoothness based on the Fourier Transform (Balasubramanian et al, 2012a).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The movement characteristic most frequently studied has been the smoothness in terms of the peak number in the hand velocity profile during the movement (Butler et al, 2010;Cacho et al, 2011;Chang et al, 2005;Fasoli et al, 2002;Kamper et al, 2002;Merlo et al, 2013;Murphy et al, 2011Murphy et al, , 2013. However, one study has shown that this metric couldn't be robust against noise or other factors, proposing an analysis of the movement smoothness based on the Fourier Transform (Balasubramanian et al, 2012a).…”
Section: Discussionmentioning
confidence: 99%
“…In reach and grasp movements, two modalities of movement time could be estimated: (i) the movement time related to reach the object to manipulate and (ii) the movement time required to stabilize the arm around the target and grasping the object (Balasubramanian et al, 2012a). This metric applied to functional movements mostly reaching movements, was used by several authors (Balasubramanian et al, 2012a;Chang et al, 2005;Fasoli et al, 2002;Jaspers et al, 2011;Van der Heide et al, 2005;Volman et al, 2002) and writing trajectories (Culmer et al, 2009). In the analysis of ADL, the total movement time was divided into phases composing the complete ADL.…”
Section: Movement Speedmentioning
confidence: 99%
See 2 more Smart Citations
“…The Manipulation Check Questionnaire, based on a previous study, 17 was administered every week (4 times total) to verify …”
Section: Secondary Outcome Measurementioning
confidence: 99%